To find the missing term in the product \((−9m^6+12m^5)(m^2+2m+1)\), we can perform the polynomial multiplication and look for the missing coefficient associated with \(m^6\).
Let's break it down step-by-step:
-
Distribute \(-9m^6\):
- \(-9m^6 \cdot m^2 = -9m^8\)
- \(-9m^6 \cdot 2m = -18m^7\)
- \(-9m^6 \cdot 1 = -9m^6\)
-
Distribute \(12m^5\):
- \(12m^5 \cdot m^2 = 12m^7\)
- \(12m^5 \cdot 2m = 24m^6\)
- \(12m^5 \cdot 1 = 12m^5\)
-
Combine all the terms:
- From the distribution, we get:
- Constant term: \(12m^5\)
- \(m^6\) terms: \(-9m^6 + 24m^6 = 15m^6\)
- \(m^7\) terms: \(-18m^7 + 12m^7 = -6m^7\)
- \(m^8\) term: \(-9m^8\)
- From the distribution, we get:
-
Putting it all together: \[ (−9m^6+12m^5)(m^2+2m+1) = -9m^8 - 6m^7 + 15m^6 + 12m^5 \]
Thus, the missing term is 15m^6.
Final answer:
Response: 15m^6